Study of Chromogenic Reaction of p-Acetylchlorophosphonazo with Lead(II) - Li, Jing-Mei; Zhai, Qing-Zhou; Li, Ying-Lai (Asian Journal of Chemistry, 2012)
In this work, p-acetylchlorophosphonazo (CPApA) and lead(II) form a blue complex in a pH 3.5 CH3COOH-CH3COONa buffer solution. A new method has been established for the determination of lead by spectrophotometry. The maximum absorption peak of Pb(II)-CPApA complex locates at 606 nm. The absorbance is linearly related over the range of 0.1-4.0 μg mL-1 at the wavelength. The apparent molar absorptivity of method is e606 nm = 2.56 × 104 L mol-1 cm-1. The method has been used to determine lead in potato. The relative standard deviation was 1.05-2.05 % for thirteen replicate determinations. The recovery of the standard addition was 99.1-105.0 %.